PERBAIKAN KUALITAS PELAYANAN JASA KEPARIWISATAAN DENGAN METODE SERVQUAL DAN QFD (Studi Kasus di Keraton Kasepuhan Kota Cirebon) - Didi Junaedi (Operations Excellence: Journal of Applied Industrial Engineering, 2015)
Abstract. Kasepuhan Palace Cirebon tourism services participate to build theeconomy of the country, especially the city of Cirebon. Therefore, in order tofurther increase the number of visits, the service quality should be improved.Using SERVQUAL method, can know the perception of service qualitykasepuhan palace Cirebon. Measuring the quality of services performed on fivedimensions that has tangible, responsiveness, assurance, reliability, and empathy.The results of this study showed that all of the dimensions are still not as expectedvisitors. The Improvement starts from the dimensions of responsiveness that havethe smallest SERVQUAL score. QFD can be analyzed using improvementpriorities according to customer needs. The most important priority that needs tobe adequate hygiene team, demolition charges, as well as the renovation andrestoration. Overall it can be proposed for improving services such as:improvement of operational systems, improvements and additions to the facility,the addition of human resources and training. The limitations is only the firstphase HOQ.Keywords: Quality, SERVQUAL, QFD, Improvement, HOQ